PROBLEMS AND PROSPECTS OF FIELD WORK TRAINING IN SOCIAL WORK EDUCATION: A REVIEW - Tippa, Naveenkumar G; R MANE, SANGEETHA (Innovare Journal of Social Sciences, 2018)
Abstract: Social work students generally considered field work training as the most important component in their professional education. In social work curriculum, practice and knowledge (theory) are two integral components in the curriculum, and yet they are often regarded as separate and so some extent antithetical (the theoreticalâ€ vs. the practicalâ€). A unique feature of fieldwork training is that training and practice take place in the same place. Hence, students are not learning aboutâ€ a practice as is the case in classroom instruction but learning inâ€ practice. Field placement is one of the most exciting and exhilarating parts of a formal social work education. It is also one of the most challenging. More than anything else, it requires students to look inside themselves and examine themselves as future social workers. However, most of the time, the students will feel better equipped for their professional career after finishing their practicum. The field work goal is to develop the student's competence in the practice of social work. Field education is an experiential form of teaching and learning that takes place in a service setting. Field work practices offered the most opportunity to understand the requirements of the people in the background of prevailing cultural traditions and values and thereby, offered opportunities to indigenize practice. It also gave opportunities for innovation. Thus, the present paper highlights and reviews on the challenges and prospects of field work training in Social Work education.